Green Human Resource Management Bundle Practices and Manufacturing Organizations for Performance Optimization: a Conceptual Model - A. Zaid, Ahmed; Talib Bon, Talib; A.M. Jaaron, Ayham (International Journal of Engineering and Technology, 2018)
As growing amount of studies have focused on green human resources management (GHRM) practices that incorporate ecological thinking, these practices are expected to affect environmental impact of organizations. GHRM can help them achieve green corporate culture and enhance their performance. In this paper, GHRM practices as a bundle is taken into account instead of individual, which give numerous benefits to the organizations. This paper reviews the literature on the relationship between GHRM bundle practices and four dimensions of organization performance. This paper also proposes a conceptual model to exhibit the relationship between GHRM bundle practices and organization performance. Hence, manufacturing firms can identify an effective approach for applying GHRM practices that contribute to organizational performance. Â Â